The taxonomy and nomenclature of the genus Aeromonas Kluyver and van Niel 1936 - SCHUBERT, RALPH H. W. (International Journal of Systematic and Evolutionary Microbiology, 1967)
SUMMARY Three aerogenic Aeromonas species are recognized: Aeromonas punctata (Zimmermann 1890) Snieszko 1957 Aeromonas hydrophila (Chester 1901) Stanier 1943 Aeromonas salmonicida (Lehmann and Neumann 1896) Griffin, Snieszko and Friddle 1953 A description of these three species is given. The nomenclatural status of the earlier species descriptions brought into connection with aerogenic aeromonads, is critically reviewed.